PENGARUH KONSERVATISMA AKUNTANSI PADA INDIKASI TIMBULNYA SENGKETA PAJAK PENGHASILAN BADAN - Warsa, Prasetya Jaya; Noviari, Naniek (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
The studies aim to verify the impact of conservatism accounting to the indication of tax income litigation. Investigation site were the whole company which were lisitng on Indonesia Stock Exchange during 2009-2013. A simple linier regression analysis was the data analysis techniques on this investigation. Three regression model used in this investigation, by reason of variable Y (indication of tax income litigation) was measured by three ratio, scilicet ratio Account Receivable/Account Payable, ratio Cash Receipt/Cash Disbursment and ratio sales/expense. Whilst the variable X (conservatism accounting) was measured in accrual model. Investigation resulted that two regression model exemplify the accounting conservatism gave a positif impact on indication of income tax litigation, whereas one of model regression refered a negative impact.
Keywords: Accounting Conservatism, indications of Income Tax Litigation